In Vivo Evaluation of Heavy Metal Decontaminated Marine Macroalgae (Ulva lactuca L.) Using Bilimbi (Averrhoa bilimbi) Juice and Its Potency As Nephroprotector - Ashfiya Hanif Hasnadewi; Mulyati Mulyati; Ardaning Nuriliani; Fajar Sofyantoro (Indonesian Food and Nutrition Progress, 2023)
Ulva lactuca is a functional food ingredient with high antioxidant content. The presence of heavy metal contaminants in natural Ulva lactuca needs to be eliminated. Ulva lactuca was investigated for its potential as a nephroprotector in female Wistar rats. The study assessed Blood Urea Nitrogen (BUN) levels, creatinine levels, and kidney histopathology. The experiment included a Group I (control), Group II (administered 1000 mg/Kg BW/day of natural Ulva lactuca), and Group III (administered 1000 mg/Kg BW/day of heavy metal decontaminated Ulva lactuca using bilimbi juice). After 30 days of oral treatment, no significant differences were observed in BUN levels before and after treatment. However, significant variations were found in Group III compared to the Group I creatinine levels after treatment. Both natural and heavy metal decontaminated Ulva lactuca showed no adverse effects on kidney function. Notably, heavy metal decontaminated Ulva lactuca exhibited improved kidney histopathology, suggesting its potential as a nephroprotector. Further research is needed to explore its broader applications in promoting kidney health.